(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The heritage formed an important tributary in the works of modern fiction, because the heritage is the cultural identity of the nation and its custodian, and he is its defender against the incoming cultures. From here, Zakaria Tamer tended in his stories to employ heritage, and Zakaria Tamer was able to mix heritage with literature, and literature with heritage, because the relationship between them is not only a relationship of creativity, but rather a relationship of integration and love, so that heritage turns in the consciousness of the writer into an active cultural component that the writer invokes intellectually. And technically to achieve degrees of change, and communicate with the recipient.